The Effect of Z907 Dye on the Performance of Solar Cells Based on the Nc-TiO2 Semiconducting Polymer Heterojunction - H. Al-Dmour (Jordan Journal of Physics, 2025)
This work studies the effect of cis-bis(isothiocyanato)(2,2'-bipyridyl-4,4'- dicarboxylato)(4,4'-di-nonyl-2'-bipyridyl) ruthenium(II) (Z907 dye) on the performance of nanocrystalline titanium dioxide (nc-TiO2)/Poly3-hexylthiophene (P3HT) heterojunction solar cells. Specifically, the P3HT/Z907dye/nc-TiO2 solar cells increase the short circuit current, Jsc, from 0.17 mA/cm2 to 0.3 mA/cm2 , the open circuit voltage, Voc, from 0.45 V to 0.7 V and the power conversion efficiency, η, from 0.03% to 0.08% compared with the P3HT/nc-TiO2 solar cells. These changes are attributed to improvements in the absorption of the light falling on the device and the generation of electron–hole pairs in the presence of the dye layer. Additionally, the dye solar cells enhance the charge transport through the interface between the nc-TiO2 and the P3HT. These results have been confirmed by studying the optical properties and the capacitance characteristics of the solar cells. Keywords: Solar cells; Capacitance; Short circuit current; Rectification; Power conversion efficiency